2020
DOI: 10.1161/cir.0000000000000920
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiorenal Protection With the Newer Antidiabetic Agents in Patients With Diabetes and Chronic Kidney Disease: A Scientific Statement From the American Heart Association

Abstract: Chronic kidney disease (CKD) with type 2 diabetes (T2D) is a major public health problem, resulting in significant cardiovascular and kidney adverse outcomes worldwide. Despite the widespread use of standard-of-care therapies for CKD with T2D over the past few decades, rates of progression to end-stage kidney disease remain high with no beneficial impact on its accompanying burden of cardiovascular disease. The advent of the newer classes of antihyperglycemic agents, including SGLT2 (sodium glucose cotransport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 80 publications
4
102
0
4
Order By: Relevance
“…Whether sufficiently robust evidence exists for low risk patients is debatable. Third, the guidance does not consider selection of individual drugs within each of the two therapeutic classes, although evidence suggests possible variation in benefits and risks 517…”
mentioning
confidence: 99%
“…Whether sufficiently robust evidence exists for low risk patients is debatable. Third, the guidance does not consider selection of individual drugs within each of the two therapeutic classes, although evidence suggests possible variation in benefits and risks 517…”
mentioning
confidence: 99%
“…[20] This principle appears to extend to patients hospitalized with COVID-19 at high risk for acute cardiorenal syndromes. [21,22] Recently, the BRACE CORONA trial showed no association between RAASi continuation and the primary outcome of death following hospital discharge for patients with COVID-19. [17] Further, a separate study demonstrated that discontinuation of RAASi therapy for patients hospitalized with COVID-19 was associated with increased risk of mortality following discharge.…”
Section: Discussionmentioning
confidence: 99%
“…В настоящее время препараты группы иНГЛТ-2 рекомендуют пациентам с СКФ от 30 мл/мин 1,73 м 2 и выше (табл. 1) [23][24][25][26][27].…”
Section: нет / Nounclassified
“…В исследовании REWIND дулаглутид снижал частоту сердечно-сосудистых событий на 12%, лираглутид в исследовании LEADER уменьшал риск ССЗ на 13%, семаглутид (в инъекциях) в исследовании SUSTAIN-6 -на 26%, семаглутид (пероральная форма) в PIONER-6 -на 21% (табл. 2) [23].…”
Section: нет / Nounclassified
See 1 more Smart Citation